Two Cheers for US Higher Education: International Implications - Brint, Steven G. (International Higher Education, 2019)
The success of US universities has derived from high levels of investment by the federal government, private donors, and individual families, combined with the propulsive force of three ultimately compatible “logics of development”: academic professionalism, technological innovation, and social inclusion. The recent history of US universities provides lessons on how to build top-tier universities and manage relations with industry. It also provides warnings about the potential for deleterious consequences when universities fail to properly manage the incorporation of underrepresented groups and undervalue undergraduate teaching.